The National Osteoporosis Foundation's position statement on peak bone mass development and lifestyle factors: a systematic review and implementation recommendations. Issue 4 (April 2016) - Weaver, C.; Gordon, C.; Janz, K.; Kalkwarf, H.; Lappe, J.; Lewis, R.; O'Karma, M.; Wallace, T.; Zemel, B.
Abstract Lifestyle choices influence 20–40 % of adult peak bone mass. Therefore, optimization of lifestyle factors known to influence peak bone mass and strength is an important strategy aimed at reducing risk of osteoporosis or low bone mass later in life. The National Osteoporosis Foundation has issued this scientific statement to provide evidence-based guidance and a national implementation strategy for the purpose of helping individuals achieve maximal peak bone mass early in life. In this scientific statement, we (1) report the results of an evidence-based review of the literature since 2000 on factors that influence achieving the full genetic potential for skeletal mass; (2) recommend lifestyle choices that promote maximal bone health throughout the lifespan; (3) outline a research agenda to address current gaps; and (4) identify implementation strategies. We conducted a systematic review of the role of individual nutrients, food patterns, special issues, contraceptives, and physical activity on bone mass and strength development in youth. An evidence grading system was applied to describe the strength of available evidence on these individual modifiable lifestyle factors that may (or may not) influence the development of peak bone mass (Table 1). A summary of the grades for each of these factors is given below. We describe the underpinning biology of these relationships as well as other factors for which a systematic review approach was not possible. Articles published since 2000, all of which followed the report by Heaney et al. [1] published in that year, were considered for this scientific statement. This current review is a systematic update of the previous review conducted by the National Osteoporosis Foundation [1]. Lifestyle Factor Grade Macronutrients Fat D Protein C Micronutrients Calcium A Vitamin D B Micronutrients other than calcium and vitamin D D Food Patterns Dairy B Fiber C Fruits and vegetables C Detriment of cola and caffeinated beverages C Infant Nutrition Duration of breastfeeding D Breastfeeding versus formula feeding D Enriched formula feeding D Adolescent Special Issues Detriment of oral contraceptives D Detriment of DMPA injections B Detriment of alcohol D Detriment of smoking C Physical Activity and Exercise Effect on bone mass and density A Effect on bone structural outcomes B Considering the evidence-based literature review, we recommend lifestyle choices that promote maximal bone health from childhood through young to late adolescence and outline a research agenda to address current gaps in knowledge. The best evidence (grade A) is available for positive effects of calcium intake and physical activity, especially during the late childhood and peripubertal years—a critical period for bone accretion. Good evidence is also available for a role of vitamin D and dairy consumption and a detriment of DMPA injections. However, more rigorous trial data on many other lifestyle choices are needed and this need is outlined in our research agenda. Implementation strategies for lifestyle modifications to promote development of peak bone mass and strength within one's genetic potential require a multisectored (i.e., family, schools, healthcare systems) approach.